Transnasal Skull Base Reconstruction Using a 3-D Endoscope: Our First Impressions - Castelnuovo, Paolo; Battaglia, Paolo; Turri-Zanoni, Mario; Volpi, Luca; Bignami, Maurizio; Dallan, Iacopo (Journal of Neurological Surgery Part B: Skull Base, 2012)
Nowadays endoscopic skull base reconstruction is safely and effectively performed by means of two-dimensional (2-D) endoscopic technique. The aim of our study is to compare our 2-D experience with the novel 3-D technology in the field of skull base reconstruction techniques. In this study four patients treated with various kinds of planned duraplasty are included. The new 3-D technology was compared with the high-definition 2-D scopes during the different steps of the procedures. The 3-D endoscopic skull base reconstruction obtained primary closure without complications in all cases. According to the subjective opinion of experienced endosurgeons, this novel technique improved depth perception, distance and size estimation, ability to identify specific anatomic structures, and hand–eye coordination. The main drawbacks detected were inferior sharpness, contrast and lighting that impaired the application of the technique in narrow sinonasal spaces. According to our preliminary impressions, 3-D endoscopic skull base reconstruction is an effective and safe procedure and could represent a significant advantage for accurate managing of the skull base region.
Keywords: three-dimensional; stereoscopic; skull base reconstruction; endoscopic; duraplasty